Century of the protest culture: Russia and Spain - Alina Koroleva (Ибероамериканские тетради)
In the 20th century the success of a protest ideology was ensured by simple, conceivable and inspiring phrases-images. But in the 21th century the images such as bright visual and musical conceptions, symbols and media stories created around them took over the word power. It is the images that form our attitude towards the reality and provoke certain actions. That is connected with social and technological transformations, which during the 20th and 21th centuries were making the process of communication more accessible and faster.